Feasibility study of inertial sensor technology on ponies for equine-assisted therapy (EAT) - Siriporn Peansukmanee (2018)
© 2017, Veteriner Fakultesi Dergisi. All rights reserved. Ponies used in equine-assisted therapy (EAT) (hippotherapy) often carry imbalanced riders, which is a cause for concern as regards the health of the ponies. A low degree of lameness or an abnormal gait is not always detectable by a veterinarian, subjectively, but this is enabled by using a motion analysis equipment. The aim of this study was to evaluate the feasibility of inertial sensor technology utilization to analyze ponies’ kinematic motion at walking gait. Ten ponies were instrumented with the inertial sensors and made to walk 20 m in two trials (departure and return) for the forelimb data set (n=10), which was then repeated in the second round for the hindlimb (n=3). The ponies were assigned three interventions: walking with no rider, walking with a rider with typical development (normal rider), and walking with a rider with physical disability (disabled rider). The movement speed, stride length, and stride duration were measured by a video camera. The limb range of motion and the angular velocity were detected by inertial sensors. The results showed that there were no significant differences in the kinematic motion of the forelimb at walking gait for all interventions and no significant differences between the left and the right forelimbs except in the case of the anterior phase of the angular velocity of the arm when walking with a disabled rider (P<0.05). The hindlimb data set was not statistically compared due to insufficient “n” number. In conclusion, the inertial sensor technology is feasible to use on pony kinematic motion, especially when the sensor is attached to the forelimb. It seems that the ponies could modify the natural kinematic motion when walking with a load on them.